ANALISIS SINONIM BAHASA ARAB ‘KALIMAH ISIM JAMID' DALAM BENTUK 'ISIM DZAT’ PADA KAMUS AL-MUNJID KARYA LOUIS MA’LUF (Lisanul Arab: Journal of Arabic Learning and Teaching, 2012)
Synonym is one linguistic phenomenon in all languages​​, including Arabic. That is, the noun (isim) in Arabic is synonymous with isim many others. However, the study of the Arabic word synonym is still lacking for language learning, because of a lack of sensitivity to study the Arabic language itself kaedah in depth and thorough. Therefore, required an explanation and analysis of synonymous words / sentences isim. In this study will be presented isim Essence synonymous sentences contained in the dictionary Al-Munjid Louis Ma'luf work and the Essence isim sentence classification in accordance with the type of synonyms.This study aimed to describe the sentences synonyms isim Essence and identify appropriate types synonym dictionary contained in Al-Munjid Louis Ma'luf work, so that people, especially Arabic language learners can learn and understand thoroughly about the sentences that have isim jamid dzaty synonym dictionary Al -Munjid.